2023
DOI: 10.2147/prbm.s404898
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Nomophobia and Its Impact on Academic Performance Among Respiratory Therapy Students in Saudi Arabia

Abstract: Background Nomophobia has been highly prevalent among health discipline students. However, there is no available data on the prevalence of nomophobia among respiratory therapy (RT) students in Saudi Arabia. Methods A cross-sectional survey using the nomophobia questionnaire (NMP-Q) was conducted and distributed using a convenience sample of RT students through an online platform (Survey Monkey) between September and November 2022. Results Ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…These findings are relatively consistent with a recent study by Aldhahir et al that examined a sizable sample (n=1428) of respiratory therapy students in Saudi Arabia and revealed that nomophobia was prevalent in nearly 97% of them, with around 48% of them experiencing moderate levels of nomophobia. 13 Corroborating our findings, many recent studies carried out among undergraduate medical students in Brazil and India indicated that approximately 99% of the entire population experienced nomophobia, with around 64–67% of the overall participants having a moderate level of nomophobia. 10 , 26 , 27 Similarly, other related studies among university students in India and Ghana have shown a prevalence rate estimated at 96–99%, with 59% of the total respondents enduring a moderate level of nomophobia.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These findings are relatively consistent with a recent study by Aldhahir et al that examined a sizable sample (n=1428) of respiratory therapy students in Saudi Arabia and revealed that nomophobia was prevalent in nearly 97% of them, with around 48% of them experiencing moderate levels of nomophobia. 13 Corroborating our findings, many recent studies carried out among undergraduate medical students in Brazil and India indicated that approximately 99% of the entire population experienced nomophobia, with around 64–67% of the overall participants having a moderate level of nomophobia. 10 , 26 , 27 Similarly, other related studies among university students in India and Ghana have shown a prevalence rate estimated at 96–99%, with 59% of the total respondents enduring a moderate level of nomophobia.…”
Section: Discussionsupporting
confidence: 87%
“… 17 Additionally, it has been reported that higher academic performance was associated with higher nomophobia scores. 13 , 18 However, no previous study has been conducted and has reported on the prevalence of nomophobia among physiotherapy students, and the extent of its association with academic performance in Saudi Arabia. Therefore, this study aims to determine the prevalence of nomophobia and assess its association with academic performance of physiotherapy students in Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%
“…Given this, future studies should assess psychophysiological markers to relate these to the experience of nomophobia. Further, a psychiatric classification requires a fully unambiguous terminology, which, however, is not the case so far: besides ‘nomophobia’ [ 1 , 23 , 24 , 25 , 26 , 27 , 28 ], others use ‘smart phone addiction’ [ 5 , 9 , 10 , 12 , 29 , 30 ] or ‘problematic or excessive smart phone use’ [ 6 , 11 , 31 , 32 ]. Fifth, a nosological category needs a clear description of the possible differential diagnostic overlap, which remains unresolved so far.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, nomophobia (no mobile phone phobia) is considered a modern age-specific anxiety for not being able to communicate, for losing connectedness, for not being able to access information, and for giving up convenience [ 1 ]. The literature is not consistent as regards the wording and the underlying theoretical psychological concepts, in that some are talking about nomophobia [ 1 , 23 , 24 , 25 , 26 , 27 , 28 ], while some claim that excessive smart phone use is considered a smart phone addiction [ 5 , 9 , 10 , 12 , 29 , 30 ] or problematic or excessive smart phone use [ 6 , 11 , 31 , 32 ]. Further, to make the point in the case, nomophobia and excessive smart phone use were associated with higher scores for emotional loneliness and insomnia among a sample of 773 students (mean age: 25.95 years; 59.6% females) [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, psychological resilience reduces the negative impact of mobile phone addiction on sleep quality [ 9 ]. However, nomophobia has increasingly received attention from researchers [ 10 , 11 ]. Nomophobia is an emerging concept closely tied to technological advances, referring to the irrational anxiety or fear that regular mobile phone users exhibit when their phone battery dies or is not immediately available due to the fear of missing messages or being unable to contact others [ 12 ].…”
Section: Introductionmentioning
confidence: 99%